2000
DOI: 10.1086/313772
|View full text |Cite
|
Sign up to set email alerts
|

Severe Pneumococcal Pneumonia in Previously Healthy Children: The Role of Preceding Influenza Infection

Abstract: An outbreak of severe pneumococcal pneumonia among children occurred in Iowa from November 1995 through January 1996. An associated outbreak of influenza disease was predominantly caused by influenza A (H1N1) for the first time since 1989. We conducted a case-control study to determine whether preceding influenza infection was directly associated with pneumococcal illness. We identified 13 children with severe pneumococcal pneumonia. Patients were more likely than control subjects to report experiencing an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
14

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(165 citation statements)
references
References 27 publications
9
141
1
14
Order By: Relevance
“…These studies were continued over twenty decades 11 , demonstrating the lethal synergism between influenza virus and Streptococcus pneumoniae that led to 100% of mortality in mice used as an experimental model. This finding has been related not only in animal models; a synergism between bacteria-influenza virus has been reported, and also observed in children with pneumococcal pneumonia that preceded influenza infection 14 Based on our data and the other reports cited, it may be concluded that co-infection between these microorganisms exacerbates respiratory infections. This situation may be aggravated in hospitalized individuals with immune depression, such as in some patients evaluated in this work.…”
supporting
confidence: 86%
“…These studies were continued over twenty decades 11 , demonstrating the lethal synergism between influenza virus and Streptococcus pneumoniae that led to 100% of mortality in mice used as an experimental model. This finding has been related not only in animal models; a synergism between bacteria-influenza virus has been reported, and also observed in children with pneumococcal pneumonia that preceded influenza infection 14 Based on our data and the other reports cited, it may be concluded that co-infection between these microorganisms exacerbates respiratory infections. This situation may be aggravated in hospitalized individuals with immune depression, such as in some patients evaluated in this work.…”
supporting
confidence: 86%
“…Bacteria such as Staphylococcus aureus and Haemophilus influenzae are known to cause postinfluenza pneumonia, but Streptococcus pneumoniae is the most prominent pathogen causing secondary bacterial pneumonia in recent decades (1). Primary infection with this pathogen is usually less severe than secondary infection (5).…”
Section: Il-10 Is An Important Mediator Of the Enhanced Susceptibilitymentioning
confidence: 99%
“…For example, patients with pneumococcal pneumonia are more likely to have had a recent influenza infection than matched controls. 62 Similarly, varicella infection increases susceptibility to group A ␀-hemolytic streptococcal infections such as necrotizing fasciitis, toxic shock syndrome, and bacteremia. 63 …”
Section: Do Vaccines "Weaken" the Immune System? Do Vaccines Increasementioning
confidence: 99%